Nitrate alleviates ammonium toxicity in wheat (Triticum aestivum L.) by regulating tricarboxylic acid cycle and reducing rhizospheric acidification and oxidative damage. (2nd December 2021) - Du, Wanying; Zhang, Yunxiu; Si, Jisheng; Zhang, Yan; Fan, Shoujin; Xia, Haiyong; Kong, Lingan
ABSTRACT: Ammonium (NH4 + ) is one of the most important nutrients required by plants. However, a high concentration of NH4 + as the sole nitrogen source suppresses plant growth. Although nitrate (NO3 − ) can alleviate NH4 + toxicity, the mechanisms underlying this ability have not been fully elucidated. In this study, wheat plants were cultivated in hydroponic solution with 7.5 mM NO3 − (control), 7.5 mM NH4 + (sole ammonium, SA) or 7.5 mM NH4 + plus 1.0 mM NO3 − (ammonium and nitrate, AN). The results showed that compared with the control, the SA treatment significantly decreased root growth, protein content and the concentrations of most intermediates and the activity of enzymes from the tricarboxylic acid (TCA) cycle. Moreover, increased the activity of plasma membrane H + -ATPase and the rate of H + efflux along roots, caused solution acidification, and increased the activity of mitochondrial respiratory chain complexes I–IV and the contents of protein-bound carbonyls and malondialdehyde in roots. SA treatment induced ultrastructure disruption and reduced the viability of root cells. Compared with the SA treatment, the AN treatment increased root growth, protein content, the concentrations of most intermediates and the activity of enzymes from the TCA cycle. Furthermore, AN treatment decreased the rate of H + efflux, retarded medium acidification, decreased protein carbonylation and lipid peroxidation in roots and relieved ultrastructure disruption and increased the viability of root cells. Taken together, these results indicate that NO3 – -dependent alleviation of NH4 + toxicity in wheat seedlings is closely associated with physiological processes that mediate TCA cycle, relieve rhizospheric acidification and decrease the production of ROS and oxidative damage.